Development paradigm in the era of globalization - ทิพย์โอสถ พระมหาปริทัศน์; Phrapalad Kriangkrai Kittisaro (Uamkham) (Journal of Contemporary Buddhist Society = JCBS, 2024)
This academic article It is a reference to the word globalization, which means progress in technology. that the humans in this world have created for the human world together It facilitates all aspects such as politics, economy, culture, technology, etc. Phenomenon that has political, economic, social and cultural relations. happening in the world has been transformed or transformed into one more closely both in terms of perception and action in various stories like never before matters or issues It happened in a very remote place and across the borders of nation-states. can be perceived and affect us quickly with the help of communication technology Make social relations on a global scale more intense. And this intensifying relationship bridges the distance in such a way that local events arise from the influence of distant events. On the other hand, local events may have consequences far away with globalization. The gap between space and time in human relations is reduced. enabling people to perceive far-flung stories At the same time, distant matters influence us. And what we find near us may have an impact on people far away.